2012
DOI: 10.1097/psy.0b013e3182408f04
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted Functional Connectivity of the Pain Network in Fibromyalgia

Abstract: These findings demonstrate that patients with FM display a substantial imbalance of the connectivity within the pain network during rest, suggesting that chronic pain may also lead to changes in brain activity during internally generated thought processes such as occur at rest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
149
1
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(168 citation statements)
references
References 48 publications
6
149
1
7
Order By: Relevance
“…59 However, fibromyalgia, which most closely resembles somatoform pain disorders in many aspects, displays a characteristic connectivity pattern during rest, as recently shown by Cifre and colleagues. 60 They found that functional connectivity of the anterior cingulate, insula and somatosensory regions with amygdala and basal ganglia was enhanced, whereas the interplay between somatosensory and default mode regions was reduced. In our study, however, a nonsignificantly higher FNC between the CIN and SMN was observed in controls, whereas the FNC of the aDMN/pDMN, aDMN/SMN, and pDMN/SMN was nonsignificantly higher in patients with somatoform pain.…”
Section: Discussionmentioning
confidence: 99%
“…59 However, fibromyalgia, which most closely resembles somatoform pain disorders in many aspects, displays a characteristic connectivity pattern during rest, as recently shown by Cifre and colleagues. 60 They found that functional connectivity of the anterior cingulate, insula and somatosensory regions with amygdala and basal ganglia was enhanced, whereas the interplay between somatosensory and default mode regions was reduced. In our study, however, a nonsignificantly higher FNC between the CIN and SMN was observed in controls, whereas the FNC of the aDMN/pDMN, aDMN/SMN, and pDMN/SMN was nonsignificantly higher in patients with somatoform pain.…”
Section: Discussionmentioning
confidence: 99%
“…As in certain chronic pain conditions (12)(13)(14), seedbased RS-fMRI studies in migraine between attacks have provided evidence of a disruption of the default mode network (DMN) (15)(16)(17)(18)(19)(20), a set of brain regions active at rest and involved in self-referential orientation and monitoring (21). Intriguingly, in chronic pain disorders, such as fibromyalgia and low-back pain, such studies have revealed a positive correlation between the intensity of pain and resting DMN connectivity with the insula (INS) (22,23) and this correlation persists with manoeuvre-induced exacerbation of pain in chronic low back pain patients (24).…”
Section: Introductionmentioning
confidence: 99%
“…También existe una moderada evidencia de que los pacientes con FM muestran una menor conectividad funcional en las áreas cerebrales que modulan el sistema descendente inhibitorio endógeno (3,11,33,47,59). Adicionalmente, hay una moderada evidencia de un marcado desequilibrio de la conectividad funcional entre los circuitos del procesamiento somatosensorial del dolor, de la auto-conciencia sensorial y de la cognición-atención hacia el dolor en los pacientes con FM (3,12,47,48). Estos datos funcionales parecen implicar cambios neuroplásticos mal adaptativos de la actividad cortical que incluyen áreas del circuito neural del dolor (90).…”
Section: Discussionunclassified
“…Así, la RMf en reposo permite estudiar la conectividad funcional cerebral intrínseca de múltiples circuitos cerebrales y su relación con el dolor espontáneo de los pacientes con FM (12,36,(47)(48)(49).…”
Section: Neuroimagenunclassified
See 1 more Smart Citation